The impact of alerting designs on air traffic controller's eye movement patterns and situation awareness. Issue 2 (1st February 2019) - Kearney, Peter; Li, Wen-Chin; Yu, Chung-San; Braithwaite, Graham
Abstract: This research investigated controller' situation awareness by comparing COOPANS's acoustic alerts with newly designed semantic alerts. The results demonstrate that ATCOs' visual scan patterns had significant differences between acoustic and semantic designs. ATCOs established different eye movement patterns on fixations number, fixation duration and saccade velocity. Effective decision support systems require human-centered design with effective stimuli to direct ATCO's attention to critical events. It is necessary to provide ATCOs with specific alerting information to reflect the nature of the critical situation in order to minimise the side effects of startle and inattentional deafness. Consequently, the design of a semantic alert can significantly reduce ATCOs' response time, therefore providing valuable extra time in a time-limited situation to formulate and execute resolution strategies in critical air safety events. The findings of this research indicate that the context-specified design of semantic alerts could improve ATCO's situational awareness and significantly reduce response time in the event of Short Term Conflict Alert (STCA) activation which alerts to two aircraft having less than the required lateral or vertical separation. Practitioner Summary: Eye movements are closely linked with visual attention and can be analysed to explore shifting attention whilst performing monitoring tasks. This research has found that context-specific designed semantic alerts facilitated improved ATCO cognitive processing by integrating visual and auditory resources. Semantic designs have been demonstrated to be superior to acoustic design by directing the operator's attention more quickly to critical situations.Abbreviations: APW: area proximity warning; ASRS: aviation safety reporting system; ATC: air traffic control; ATCO: air traffic controller; ATM: air traffic management; COOPANS: cooperation between air navigation service providers; HCI: human-computer interaction; IAA: irish aviation authority; MSAW: minimum safe altitude warning; MTCD: medium-term conflict detection; SA: situation awareness; STCA: short term conflict alert; TP: trajectory prediction